FROM DATA TO DECISIONS LEVERAGING ADVANCED MIS FOR STRATEGIC BUSINESS INSIGHTS - Tekat Sukomardojo; Rahmat Purbandono H; Endang Fatmawati; Sri Wulan Windu Ratih; La Ode Almana (UIN Sunan Gunung Djati Bandung, 2024)
In today's rapidly evolving business landscape, Management Information Systems (MIS) play a crucial role in transforming raw data into strategic business insights. This study explores the impact of advanced MIS on decision-making processes within organizations, highlighting the integration of data analytics, business intelligence, and decision support systems. By examining various case studies and empirical data, the research illustrates how companies can leverage MIS to gain a competitive advantage, improve operational efficiency, and foster innovation. The findings suggest that the effective use of MIS not only enhances strategic planning but also facilitates real-time decision-making, thereby driving business growth and sustainability. This paper aims to provide a comprehensive understanding of the mechanisms through which MIS can be utilized to optimize business outcomes and support strategic initiatives.